2022
DOI: 10.1370/afm.2807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Electronic Consultation Service for COVID-19 Care

Abstract: PURPOSE COVID-19 has increased the need for innovative virtual care solutions. Electronic consultation (eConsult) services allow primary care practitioners to pose clinical questions to specialists using a secure remote application. We examined eConsult cases submitted to a COVID-19 specialist group in order to assess usage patterns, impact on response times and referrals, and the content of clinical questions being asked.METHODS This was a mixed-methods analysis of eConsult cases submitted between March and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…We screened 181 full-text articles, of which we excluded 108 records after applying exclusion criteria. A total of 72 studies were eligible for data extraction (Figure).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We screened 181 full-text articles, of which we excluded 108 records after applying exclusion criteria. A total of 72 studies were eligible for data extraction (Figure).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 72 studies, 34 (47%) were conducted in the US, 31 (43%) in Canada,and 7 (10%) in the rest of the world (Table 2). Of the 72 studies, 31 (43%) focused on multispecialty services, and 14 (19%) focused on internal medicine or a subspecialty of internal medicine .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2021 pilot study on the use of remote access to specialists in Queensland showed that it is feasible in Australia and reduced the need for a face-to-face referral by about 85% (Job et al 2021). A similar study in Ontario, Canada, during the COVID-19 pandemic suggested that telemedicine consults can prevent about 25% of what would otherwise be in-person specialist visits, thus freeing up space in the health system (Singh et al 2022).…”
Section: Discussionmentioning
confidence: 99%